Analysis of Risk Management in Construction of Bin Qasim Industrial Park, Karachi. - Areeba Asif Baig; Quratulain Khalid; Muhammad Mutasim Billah Tufail (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
With ongoing globalization and trade liberalization, most economies are now focusing on export-led development strategies. In this framework, industrial parks are considered to be essential resources for local industrial development. Clustering businesses within industrial parks offer various benefits for small, medium, and large enterprises. These advantages include access to public infrastructure, cost-saving opportunities through shared facilities, and enhanced access to research and vocational/technical resources, among other essential inputs (Abuja and Eaton, 2010). This in turn makes their products competitive in the domestic and international markets. A project Bin Qasim Industrial Park (BQIP) is an initiative in this regard an urban area. The project has been delayed for almost 2 years due to multiple reasons and not a well-controlled risk management process. Therefore, the business objectives have been reduced but somehow, the project is successful because the long-term goal has been achieved and still, organizations get some revenue. In this research, SWOT analysis has been revised against the need for such industrial parks in urban areas. An effort has also been made against findings of potential risks involved in establishing such large-scale industrial parks, risk identification, risk assessment, and their mitigation or response. Therefore, it has been summarized that a well-planned Industrial Zone for all categories especially an automotive-based industrial zone could cater to the needs of its potential investors and hence encourages them to invest capital in setting up industries suitable to the area. This study helps in risk management and the establishment of such projects.